2012
DOI: 10.1097/sla.0b013e31824682f4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Distal Gastrectomy for Gastric Cancer

Abstract: LDG can be performed safely with a shorter hospital stay and fewer complications than open surgery. The long-term significance of a difference of less than 5 nodes in the number of harvested lymph nodes remains unclear. Lymph node staging appears to be unaffected. These results need to be validated in Western patients with advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
130
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(144 citation statements)
references
References 100 publications
3
130
0
11
Order By: Relevance
“…Significant reductions in the use of analgesics and narcotics, more rapid recovery of intestinal movement, and faster return to normal diet in LAG group together contribute to a reduction in hospital stay, although local hospital policies are different worldwide. These results concur with previous published analyses (Hosono et al, 2006;Liang et al, 2011;Ding et al, 2012;Vinuela et al, 2012), making the meta-analysis of short-term outcomes unnecessary. This study (815 patients) focused on the surgical safety and oncologic results for LAG with extended lymphadenectomy of seven studies comparing laparoscopic with open surgery for mainly AGC; and confirmed that LAG for AGC achieved equivalent morbidity rates.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Significant reductions in the use of analgesics and narcotics, more rapid recovery of intestinal movement, and faster return to normal diet in LAG group together contribute to a reduction in hospital stay, although local hospital policies are different worldwide. These results concur with previous published analyses (Hosono et al, 2006;Liang et al, 2011;Ding et al, 2012;Vinuela et al, 2012), making the meta-analysis of short-term outcomes unnecessary. This study (815 patients) focused on the surgical safety and oncologic results for LAG with extended lymphadenectomy of seven studies comparing laparoscopic with open surgery for mainly AGC; and confirmed that LAG for AGC achieved equivalent morbidity rates.…”
Section: Discussionsupporting
confidence: 82%
“…There are few reports related to the efficacy of LAG in the management for AGC. Regarding the inclusion criteria used to select studies, the recent reports (Hosono et al, 2006;Liang et al, 2011;Ding et al, 2012;Vinuela et al, 2012) included patients with EGC. AGC has rarely been evaluated rigorously in a study.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of patients had EGC and therefore comparison to a Western population case-mix is difficult. Results further showed additional benefits of fewer overall and minor complications, shorter lengthof-stay (weighted mean difference, 3.6 d) and less blood loss [59] . Also, longer operation time and lower number of harvested lymph nodes was reported for laparoscopic gastrectomy.…”
Section: Laparoscopic Surgerymentioning
confidence: 92%
“…Also, longer operation time and lower number of harvested lymph nodes was reported for laparoscopic gastrectomy. Several other reviews and meta-analyses have been published on this subject since (Table 3) [59][60][61][62][63] . The general conclusion of these studies is that laparoscopic approach offers improved recovery after surgery at no compromise of morbidity and mortality.…”
Section: Laparoscopic Surgerymentioning
confidence: 99%
See 1 more Smart Citation